The politics of public housing : Black women's struggles against urban inequality - Williams, Rhonda Y. (Transgressing boundaries., 2004)
Black women have traditionally represented the canvas on which many debates about poverty and welfare have been drawn. For a quarter century after the publication of the notorious Moynihan report, poor black women were tarred with the same brush: "ghetto moms" or "welfare queens" living off the state, with little ambition or hope of an independent future. At the same time, the history of the civil rights movement has all too often succumbed to an idolatry that stresses the centrality of prominent leaders while overlooking those who fought daily for their survival in an often hostile urban land.